Inclusive finance and its impact on the microemprendimiento in the city of Loja, Ecuador (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
This article aims to analyze the impact of microcredit implemented by Credit Associative Human Development (CDHA) in micro-enterprise activities. Knowing if you are generating in CDHA beneficiaries entrepreneurial development, which is based on the ability to create and develop micro-enterprise activities sustainable and dynamic, is to determine if it has generated a positive economic impact on the sector analyzed microcredit in the household economy of the people who perceive it.
Keywords: credit human development; inclusive finance; microcredit; popular; solidarity finance